How can CEOs influence HRM implementation? Unfolding top management’s role in HRM - Mirfakhar, A. (2023)
This paper investigates how CEOs can influence the implementation of HRM policies in their organizations. It does so by comparing the HRM implementation roles of the same CEO in two different companies as well as those of different CEOs in the same firm. Based on the findings, the study inductively develops a model that describes different types of CEO direct and indirect influence, unfolding the generic label of CEO “support” into a wide catalogue of actions, and identifying further behaviours other than support. The results also challenge some established ideas, such as the view of CEOs’ HRM role solely as strategic decision makers, or that CEO influence necessarily involves overt action. Finally, our findings open several avenues for future research on a relevant and, so far, underdeveloped topic.